Determinan Kejadian Preeklampsia Di RSD Kalisat Jember - Herlidian Putri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
Hypertension in pregnancy is 5-15% complicating pregnancy and is one of the three highest causes of maternal and maternal morbidity and mortality. The purpose of this study was to analyze the determinants of the incidence of preeclampsia in the Kalisat Hospital in Jember Regency in 2018. The study design used a case control study approach. The number of samples in this study were 74 cases of preeclampsia that occurred in 2018 and control samples namely 74 pregnant women who did not experience preeclampsia who had a gestational age or time of delivery that was close to women who had preeclampsia. The instrument for collecting data is the research data collection sheet with medical record data sources. Analysis of the data carried out was descriptive analysis and multivariate analysis using Chi-Square formula. The results obtained p-value 0.037 <α 0.05 for the variable age of the mother, p-value 0.023 <α 0.05 for the variable parity, p-value 0,000 < α 0.05 for gemeli variable which means that Ho is rejected, then there is an influence of age determinant of pregnant women with preeclampsia, parity of pregnant women with preeclampsia and ameliorated pregnant women with preeclampsia on the incidence of preeclampsia. Based on the results of the above research, detection efforts should be made as early as possible very important for pregnant women